2022
DOI: 10.3346/jkms.2022.37.e118
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Physical and Mental Health and Healthy Eating Habits During the COVID-19 Pandemic in Korea

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has disrupted the lives of people around the world since 2020. This study aims to reveal perceived impact of the coronavirus pandemic on physical and mental health and eating behaviors among people with disabilities and without disabilities in South Korea, as compared to other countries. Methods A secondary analysis of a prospective cross-sectional study which was conducted with a web-based global survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…En cuanto a los estilos de vida saludable determinado por el formulario Fantástico, se encontró que, a mayor puntaje en dicha prueba, los puntajes de depresión se sitúan en leve o mínimo, siendo proporcional el EVS con una menor posibilidad de presentar síntomas depresivos. Estos hallazgos son similares a los encontrados (Milojevich & Lukowski (2016); Ruiz-Hernández, Guillén, Pina & Puente-López, (2022); Tuakli-Wosornu, et al, (2022);Ðorðić, et al, (2022)).…”
Section: Discussionunclassified
“…En cuanto a los estilos de vida saludable determinado por el formulario Fantástico, se encontró que, a mayor puntaje en dicha prueba, los puntajes de depresión se sitúan en leve o mínimo, siendo proporcional el EVS con una menor posibilidad de presentar síntomas depresivos. Estos hallazgos son similares a los encontrados (Milojevich & Lukowski (2016); Ruiz-Hernández, Guillén, Pina & Puente-López, (2022); Tuakli-Wosornu, et al, (2022);Ðorðić, et al, (2022)).…”
Section: Discussionunclassified
“…A different study reported a significant increase in the cases of depression (14%) in American (USA) adults during the pandemic with respect to previous years (9%) [18]. In the same vein, even in countries such as Korea, where the perceived physical health was maintained to a great extent thanks to the fact that the government allowed citizens to perform outdoor activities wearing masks and home exercise was promoted through online programmes, mental health was significantly affected [19]. Moreover, a study conducted with a Spanish population reported a decrease in physical activity and greater adherence to the Mediterranean diet during the lockdown [20].…”
Section: Introductionmentioning
confidence: 98%
“…They found no significant differences in the physical health and eating habits of individuals with and without disabilities in South Korea during the lockdown. However, they found that perceived mental health was worse during the lockdown for those with and without disabilities ( 16 ). There is a female preponderance in Mexico.…”
Section: Introductionmentioning
confidence: 99%